Effect of microbial transglutaminase addition on reconstructed frozen rainbow trout (Oncorhynchus mykiss) meatballs’ quality - Kocatepe, D; Corapci, B; Altan, CO; Kőstekli, B; Turan, H (Journal of the Hellenic Veterinary Medical Society, 2024)
In this study, MTGase (Control (without enzyme), A-0.5% MTGase (Group A), and B-0.8% MTGase (Group B) were added to rainbow trout meatballs at two different rates and the samples were stored at -18±1°C. The chemical (TVB-N, TBARS), physical (pH, water activity, color, texture, and cooking loss), microbiological (TMAB, TPAB, TYM, TCB, TAB, E. coli, and S. aureus), and sensory properties of the trout meatballs were examined for 210 days. The TVB-N and TBARS values remained within the limit values during frozen storage. The pH and cooking loss values of the control group were different from those of Groups A and B. The water activity values generally remained stable. The L* and a* values were affected by the addition of MTGase. Moreover, the textural properties and sensory quality of the trout meatballs improved. During the frozen storage, the limit values were not exceeded in all groups, except for the TCB values.